Pyridoxine non-responsive p.R336C mutation alters the molecular properties of cystathionine beta-synthase leading to severe homocystinuria phenotype - Duaa W. Al-Sadeq (10976754) (2022)
The prevalence of homocystinuria in Qatar is 1:1800, mainly due to a founder missense mutation p.R336C. The cystathionine beta-synthase (CBS) R336C mutant was bacterially expressed, purified and its molecular properties were compared to CBS wild type (WT) recombinant protein. Our data revealed that p.R336C mutation results in a dramatic reduction (∼86%) of CBS enzymatic activity. Circular Dichroism experiments suggested that the p.R336C mutation does not significantly alter the secondary structure of the CBS protein. CD spectra also revealed distinct differences in the thermal unfolding mechanisms of CBS WT and R336C mutant protein species. Chemical denaturation experiments indicated that the WT CBS protein is thermodynamically more stable than the R336C mutant, suggesting a destabilizing effect of the p.R336C mutation. This study provides mechanistic insight into the pathogenicity of the p.R336C mutation that leads to a severe homocystinuria phenotype. Other Information Published in: Biochimica et Biophysica Acta (BBA) - General Subjects License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bbagen.2022.130148 Additional institutions affiliated with: Hamad Medical Corporation, Hamad General Hospital - HMC, Women's Wellness and Research Center - HMC, Interim Translational Research Institute - HMC